Screening, docking, and molecular dynamics analysis of Mitragyna speciosa (Korth.) compounds for targeting HER2 in breast cancer - Nabila Hadiah Akbar; Farendina Suarantika; Taufik Muhammad Fakih; Ariranur Haniffadli; Khoirunnisa Muslimawati; Aditya Maulana Perdana Putra (Current Research in Structural Biology, 2025)
Breast cancer remains the most commonly diagnosed cancer among women worldwide, with approximately 2.3 million new cases reported in 2022. In the United States alone, an estimated 310,720 new cases of female breast cancer are expected in 2024. HER2-positive breast cancer, characterized by the overexpression of the human epidermal growth factor receptor 2 (HER2), accounts for about 20 % of all breast cancer cases. The development of anti-HER2 therapies has significantly improved survival rates for patients with HER2-positive breast cancer. In this study, we employed in silico methods to evaluate the potential of natural alkaloids, Mitragynine and 7-Hydroxymitragynine, as HER2 inhibitors. Molecular docking revealed binding energies of −7.56 kcal/mol and −8.77 kcal/mol, respectively, with key interactions involving residues such as Leu726, Val734, Ala751, Lys753, Thr798, and Asp863. Molecular dynamics simulations demonstrated the stability of all three complexes, including Mitragynine, 7-Hydroxymitragynine, and Native (SYR127063), over the simulation period. Mitragynine exhibited stronger interaction stability, supported by a higher hydrogen bond occupancy of 39.19 %, compared to 4.32 % for 7-Hydroxymitragynine, while Native (SYR127063) displayed the highest occupancy at 49.66 %. MM-PBSA analysis further validated these findings, with Native (SYR127063) exhibiting the most favorable total binding energy of −163.448 ± 17.288 kJ/mol, followed by Mitragynine at −112.33 ± 22.41 kJ/mol, and 7-Hydroxymitragynine at −103.56 ± 15.61 kJ/mol. ADMET, physicochemical properties, and drug-likeness evaluations indicated that all compounds satisfy Lipinski, Ghose, Veber, Egan, and Muegge rules, confirming their suitability as lead-like molecules. Based on these findings, Mitragynine and 7-Hydroxymitragynine are promising candidates for HER2-targeted breast cancer therapy, with further experimental validation recommended to confirm their clinical potential.